Effects of organic and other management practices on soil nematode communities in tea plantation: a case study in southern China. Issue 4 (27th June 2014) - Li, Xingyue; Liu, Qizhi; Liu, Zhilong; Shi, Wangpeng; Yang, Daowei; Tarasco, Eustachio
Abstract: Four major tea management practices (organic, pollution‐free, conventional, and semi‐natural) are employed in Chinese tea plantations at present. These practices can induce changes in the physiochemical parameters, microorganism community and enzyme activity in tea plantation soil. However, understanding of their effects on soil nematodes is still scarce. This study aimed to investigate whether and how different management practices affect the biodiversity, function, and structure of soil nematode communities in tea plantation habitats. The soil nematode community structures and ecological indices were determined from the soil samples collected more than 6 y after their respective farming practices were first applied, and different management practices did not greatly affect soil nematode community evenness or species diversity, but organic practice increased nematode trophic diversity, common species diversity, and species richness. Pollution‐free practice considerably increased fungivorous nematodes, and both pollution‐free and conventional practice decreased bacterivorous nematodes markedly in the subsurface layers of soil. Predator and omnivorous nematodes were found to be more abundant in semi‐natural plantation. Organic practice was more sustainable and suitable for tea cultivation, with the greatest biodiversity, best nutrient conditions, higher and more stable C/N ratio and lower interference in the food web.